Environmental profile of natural biological vanillin production via life cycle assessment. (25th July 2021) - Zhao, Xinyue; Chen, Juntong; Meng, Xiangwei; Li, Lanqing; Zhou, Xue; Li, Jianguo; Bai, Shunwen
Abstract: Natural vanillin production (NVP) offers the possibility of using biological synthesis pathways, such as those involving physics, enzymes and microbiology, rather than relying on petroleum derivatives as major raw materials. However, such NVP pathways do not inevitably lead to improved environmental performance, especially considering that many pathways are constructed based on molecular methods involving high consumption of materials and energy. This study aimed to apply life cycle assessment (LCA) to evaluate eight NVP pathways. The results indicated that biosynthesis-based pathways using substrates such as glucose, eugenol, isoeugenol and ferulic acid demonstrated preferable environmental performance in most of the midpoint impact categories. According to endpoint-based LCA results, human health was the environmental aspect most heavily affected, with human toxicity accounting for the highest contributions (77.57%–78.71%). For the identified key environmental contributors, electricity use accounted for the highest environmental burdens in the pathways that utilized eugenol or isoeugenol, while chemical consumption generated the maximum impacts in the pathways that utilized glucose or ferulic acid. From the perspective of future development, improved environmental performance for NVPs could be achieved if future technological advancement offers economy of scale or if the electricity scheme accelerates the transition towards cleaner energetic systems. Finally, this study found that developed countries had more advantages for advancing NVP pathways towards more environmental friendly options since they were more likely to execute new energy policies and lead the international development of renewable energy. Highlights: Life cycle assessment of natural vanillin synthesis process was carried out for the first time. Human toxicity potential was the most influential impact category. Electricity use was the highest environmental burdens for eugenol and isoeugenol pathways. Chemical consumption was the maximum impacts for glucose and ferulic acid pathways. Energetic system evolution could improve the future environmental performance.